Presenteeism: The conceptualization of the internal & external factors - Ruzainy Alwi M.N.; Toolib S.N. (Mattingley Publishing, 2023)
Personnel; Societies and institutions; External factors; Factor; Presenteeism; Productivity loss; Work environments; Productivity